Adsorption of copper, nickel and lead ions from synthetic semiconductor industrial wastewater by palm shell activated carbon - Onundi, Yusuf Bamidele; Al-Mamun, Abdullah; Al-Khatib, Ma'an Fahmi Rashid; Ahmed, Yehya M. (Center for Environmental and Energy Research and Studies, 2010)
Granular activated carbon produced from palm kernel shell was used as adsorbent to remove copper, nickel and lead ions from a synthesized industrial wastewater.Laboratory experimental investigation was carried out to identify the effect of pH and contact time on adsorption of lead, copper and nickel from the mixed metals solution. Equilibrium adsorption experiments at ambient room temperature were carried out and fitted to Langmuir and Freundlich models. Results showed that pH 5 was the most suitable, while the maximum adsorbent capacity was at a dosage of 1 g/L, recording a sorption capacity of 1.337 mg/g for lead, 1.581 mg/g for copper and 0.130 mg/g for nickel. The percentage metal removal approached equilibrium within 30 min for lead, 75 min for copper and nickel, with lead recording 100 %, copper 97 % and nickel 55 % removal, having a trend of Pb2+ > Cu2+ > Ni2+ . Langmuir model had higher R2 values of 0.977, 0.817 and 0.978 for copper, nickel and lead respectively, which fitted the equilibrium adsorption process more than Freundlich model for the three metals